Social work practice with families and children - Maluccio, Anthony N.; Pine, Barbara A.; Tracy, Elizabeth M. (Foundations of social work knowledge., 2002)
This book emphasizes family-centered, social network, and school-based interventions in the preparation of social workers for direct and indirect practice with clients from vulnerable populations, especially the poor, people of color, and recent immigrant groups. With an eye to recent changes in social work practice and service delivery, including the impact of welfare reform and managed care on vulnerable families and children, Social Work Practice with Families and Children helps social work students and practitioners understand the increasingly complex needs of their clients. Three valuable.